LASER INFORMATION SYSTEM FOR MONITORING GLUE EVAPORATION DURING DRYING (Computer systems and information technologies, 2025)
In the context of advancing technologies in printing, materials processing, and chemical production, there is a growing demand for precision in monitoring volatile emissions generated during drying processes. Conventional control methods often lack the speed, sensitivity, or selectivity required for real-time analysis of adhesive evaporation products, particularly in dynamic industrial environments such as book block drying chambers.This study substantiates the development of laser-based resonance photometric systems for evaluating the concentration of evaporated chemical components from adhesive mixtures. A methodological framework is proposed for implementing dual-channel laser photometry, enabling non-contact, rapid, and spatially resolved assessment of volatile content. The structure and operating principles of a laboratory-grade concentration meter are presented, incorporating semiconductor lasers, photodetectors, signal processing units, and intelligent control agents.Special attention is given to the physical and quantum-chemical interactions of laser beams with aqueous media, as well as to the solubility dynamics of adhesive components under thermal influence. A two-stage selective photoionization approach is introduced to enhance signal amplification through resonance effects, enabling more precise quantification of emissions.The proposed methods can be applied not only to printing production environments but also to broader ecological monitoring tasks involving laser-based diagnostics of airborne and liquid-phase contaminants. These technologies contribute to the development of next-generation intelligent sensing systems capable of supporting environmental safety and process optimization.
Keywords: photometry; laser; resonance phenomena; quantum interaction; concentration; drying; adhesive